Los Angeles Ccap - McPHILAMY, W. Patrick (Revista Amagis Jurídica, 2024)
This Climate Change Action Plan (CCAP) was created to address climate change issues confronting the City of Los Angeles (Los Angeles or the City). Los Angeles faces serious risks and adverse impacts to the health, safety, and welfare of its residents, environment, and economy from climate change (LOS ANGELES, 2014; UNIVERSITY, 2013; WILLIAMS et al., 2015). In Los Angeles, climate change is expected to worsen air pollution, triple the number of extremely hot days above 95 o F, and increase wildfires during the next 30 years, presenting grave public health issues such as increased respiratory diseases, poor water quality, and illnesses and deaths caused by heat and vector-borne diseases (LOS ANGELES, 2014). Climate scientists have suggested that human activities will continue to contribute to extreme weather and drought in California in future years (National Oceanic Atmospheric Administration - NOAA, 2015, citing Belmecheri, 2015). The City’s coastal infrastructure is at risk due to anticipated sea level rise, namely, the City’s wastewater management, stormwater management, and potable water systems, and City roads (UNIVERSITY, 2013). Moreover, coastal flooding could have an adverse impact on the economies of beach communities in Los Angeles, accounting for $16.5 billion in expenditures in 2012 (UNIVERSITY, 2013, p. 2). In order to mitigate those risks and impacts, this plan presents various pathways for Los Angeles to achieve carbon neutrality by 2050.